DEVELOPING READING SKILLS IN EFL LEARNERS - Xujaqulova Aziza Uzbekistan State World Languages University The Second English Faculty 2nd-year student (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Reading is a fundamental language skill that plays a central role in second and foreign language learning. For learners of English as a Foreign Language (EFL), developing effective reading skills not only enhances vocabulary and grammar but also contributes to cognitive growth and language fluency. However, reading in a foreign language can be a challenging task due to limited exposure, lack of vocabulary, and insufficient practice. This article explores the nature of reading in EFL contexts, discusses the main challenges that learners and teachers face, and provides a set of practical, classroom-tested strategies to support young learners in becoming confident and active readers. The article also highlights the importance of motivation, the role of teachers, and the value of integrating reading with other skills.